Pedagogical aspects of ecoGothic elements in Ruskin Bond’s novellas - Jain, Priyank; Anita Harris Satkunananthan, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article examines the pedagogical aspect of the ecoGothic elements in Ruskin Bond’s fiction, particularly the three novellas chosen to be highlighted: Angry River (Flood), Dust on the Mountains (Deforestation in the Mountains) and Tiger, Tiger Burning Bright (Wildlife Conservation) . Even his poems such as “The Pool” and “Parts of Old Dehra” carry the same sombre tone. This article will be analysing these stories, mapping their Gothic tropes such as ‘Burkean Grief” and ‘sympathy for the devil”. In so doing, this article will be highlighting the pedagogical importance of Bond’s work utilising an ecoGothic perspective married to a postcolonial Gothic pedagogical approach. The aim is to initiate a discourse around the pedagogical benefits of reading Ruskin Bond’s novella from an ecoGothic perspective in order to inculcate an inter-disciplinary approach towards environment conservation. This article will mainly be using Gina Wisker for the postcolonial Gothic pedagogical framework and Thomas Nelson for his methodology of using education to combat ecological crises. The findings reveal that the conflict between humans and nature in Bond’s fictions connect to a stronger underlying theme in Indian EcoGothic fiction in relation to climate change.